EMOTIONAL INTELLIGENCE EDUCATION VERSION OF THE QUR'AN - Abdul rohman (An-Nahdlah: Journal of Islamic Studies, 2023)
Al-Qur'an is one of the sources of Islamic law which is full of wisdom other than As-Sunnah (Hadith). The values contained in it always inspire readers and "understanders" to be able to interpret life more deeply because every verse is never separated from the learning element from Khaliq for creatures. The emotions of creatures are one of the objects touched by the Qur'an with all the glory of its verses that can influence "emotions" so that they can get used to commendable behavior to be applied in everyday life. Emotional intelligence can be defined as the ability to sense, understand, and effectively apply the power and sensitivity of emotions as a source of human energy, information, connection and influence. The results showed that Emotional Intelligence Education in Tafsir Al Misbah was able to identify various dimensions of emotional intelligence, namely the Form of Consistent Attitude (Istiqomah), Humble Attitude (Tawadhu '), Form of Effort and Surrender (Tawakkal). The Form of Sincerity (Sincerity).